Analisis Ketidakseimbangan Beban Jaringan Distribusi Tegangan Rendah menggunakan ETAP - Rizky, Rizky Tambara Ginting; Zulfahri, Zulfahri; Arlenny, Arlenny (SainETIn : Jurnal Sains, Energi, Teknologi, dan Industri, 2022)
In order to meet the demand for electrical energy, the load distribution was initially evenly distributed, but due to the unequal installation or usage time. This causes a load imbalance due to inconsistent installation time and usage of these loads, which has an impact on the supply of electrical energy. The load imbalance between each phase (R phase, S phase and T phase) causes current to flow in the neutral section of the transformer. PLN as a supplier of electricity for the community must be able to serve the electricity needs of the community with a good and good quality level. In order to get efficient and effective work results, high productivity is needed. From the load imbalance analysis at the ST 263 distribution substation, Jalan Kaharuddin Nasution, Pekanbaru, against the neutral current, there are 0.383 kW losses during the day and 0.662 kW at night, from simulations and calculations using stages the losses during the day are 0.344 kW and 0.583 kW at night. day. There is a difference of 0.023% during the day and 0.047% when calculating the measurements with the stages. Based on the load imbalance standard, the ST 263 200 kVA transformer still meets the IEEE std 446-1995 standard, which is 5% - 20%. The greater the IN neutral current flowing in the transformer neutral conductor, the greater the losses generated.